Movements and Parties: An Introduction - Manuela Caiani (Partecipazione e Conflitto, 2023)
The article provides an analytical introduction to the Symposium devoted to Sidney Tarrow's "Movements and Parties. Critical Connections in American Political Development". First, it discusses the relevance of the book with regards to the Movement-Parties scholarship. Second, it presents the content of the Symposium, focusing on the main arguments developed by the various authors.